Experimental evaluation of predator exclosures on nest, chick, and adult survival of piping plovers. Issue 1 (30th December 2021) - Anteau, Michael J.; Swift, Rose J.; Sherfy, Mark H.; Koons, David N.; Ellis, Kristen S.; Shaffer, Terry L.; Toy, Dustin L.; Ring, Megan M.
Abstract: Species of conservation concern often receive intensive management to improve vital rates and facilitate recovery. Piping plovers ( Charadrius melodus ) are federally listed in the United States and concerns over nest depredation have prompted widespread use of plover‐permeable predator exclosures placed around nests (0.5–2‐m radius). While effectiveness of exclosures for improving nest survival has been demonstrated, concerns remain about decreased chick survival (through predator cueing or density‐dependent processes) or increased vulnerability of adults to predation (ambush as adult leaves exclosure). Either one of these concerns could demographically outweigh the benefits of increased nest survival. During 2014–2016, we conducted an experiment designed to evaluate survival of uniquely identified nests ( n  = 418), chicks ( n  = 453), and adults ( n  = 367) at wetlands across the Northern Great Plains, USA. We assigned wetlands ( n 2014  = 26, n 2015  = 28, n 2016  = 25) into 2 groups: wetlands in which half of the nests received exclosures and wetlands in which none of the nests received exclosures. Exclosed nests had greater cumulative survival (0.73 [85% CI = 0.70–0.77]) than unexclosed nests at treatment wetlands (0.58 [0.54–0.62]) or unexclosed nests at control wetlands (0.52 [0.49–0.56]). Survival to fledging was highest for chicks hatched from exclosed nests (0.51 [0.47–0.56]), and similar between chicks hatched from unexclosed nests at treatment (0.34 [0.30–0.39]) and control (0.37 [0.32–0.42]) wetlands. Cumulative survival of adults during incubation varied by exclosure status, but adults associated with exclosed nests (0.90 [0.88–0.93]) and unexclosed nests at treatment wetlands (0.89 [0.86–0.92]) had greater survival than those associated with unexclosed nests at control wetlands (0.75 [0.64–0.84]). Adult annual survival rates varied by year (0.79–0.95) but not by exclosure status. The positive influence of exclosures on nest survival was not offset by a reduction in chick or adult survival, indicating that exclosures are a viable tool for piping plover conservation. Abstract : We conducted an experiment to evaluate if predator exclosures, placed around a nest, were effective at increasing nest survival of piping plovers; we also evaluated if there were any detrimental impacts of exclosures on chick and adult survival. Nest exclosures had a positive influence on nest survival that was not offset by a reduction in chick or adult survival, indicating that exclosures are a viable tool for plover conservation.